Research on Innovative Pathways for Blended Teaching Models in Higher Vocational English Oral Communication through Digital Technology Empowerment—A Case Study of Higher Vocational Institutions in the Greater Bay Area (Contemporary Education and Teaching Research, 2026)
At present, digital technologies have been widely integrated into the field of education, bringing about profound changes in both the instructional forms and pedagogical models of English-speaking instruction in higher vocational colleges. Blended learning, which combines online and offline instructional approaches, effectively addresses common challenges in traditional vocational English-speaking classrooms, such as low levels of student engagement and limited opportunities for oral output. Taking higher vocational colleges in the Guangdong–Hong Kong–Macao Greater Bay Area as the research context, this study first examines the value and current status of digitally empowered blended English speaking instruction, and summarizes the major problems encountered in practical teaching implementation. It then systematically explores the implementation pathways of a digitally empowered blended teaching model for vocational English speaking from several perspectives, including the reconstruction of teaching resource systems, integrated design of the teaching process, establishment of high-frequency oral output mechanisms, innovation in teaching evaluation models, and transformation of teachers’ roles. This study aims to provide practical references for optimizing English-speaking instructional models in higher vocational education and enhancing overall teaching quality.